Online Adolescent Suicide Risk Assessment - Virginia Sue Biddle (Association of American Medical Colleges, 2013)
Abstract This web-based suicide risk assessment training module is geared towards primary care providers and other clinicians who want to identify youth at risk for suicide in their practices. The program focuses on the assessment of background and subjective risk factors using the well-known Home, Education, Activities, Drug use and abuse, Sexual behavior, and Suicidality (HEADSS) interview instrument for psychosocial risk assessment. It is designed for providers who need basic knowledge concerning suicide risk assessment. Review questions that users must answer are displayed periodically throughout the module. These questions reinforce the content and help users assess their learning. A pilot study was conducted to test the effectiveness of the program in increasing the knowledge of 26 graduate nurse practitioner and nurse midwife students in assessing adolescents for suicide risk. A pre-and posttest design and statistical analysis using a paired t-test (to test the difference between mean scores for the pretest and posttest) were employed to determine the effectiveness of the training program. Pre- and posttest questions from videotaped vignettes were grouped into the following subscales: setting the stage, psychosocial assessment, depression assessment, triage, recognition, and intervention. Using an alpha level of .05, the paired t-tests for each subscale, as well as all subscales combined, were statistically significant. The results indicated that student knowledge regarding assessing adolescents for suicide risk increased at a statistically significant level after participating in the training. The online suicide risk assessment training has been completed by 201 pediatric nurse practitioners or other advanced practice nurses via the Web site of the National Association of Pediatric Nurse Practitioners. They rated the program 4.5 or higher on a 5-point Likert scale for meeting each educational objective and their own expectations, as well as for appropriateness of content, and their ability to integrate concepts learned into clinical practice. All scores improved from the pretest to the posttest. Of the 29 participants who were willing to be surveyed at a later date, all indicated that they made changes to their clinical practice after the training. Eighty-five percent reported that they made at least four changes and 15% reported that they made at least one change. The significance of the program is that it provides students and clinicians with a way to learn basic suicide risk assessment in an online format, enables them to apply knowledge gained to clinical scenarios via videotaped vignettes, and allows them to assess their knowledge before and after the training.